The Role of Mindfulness as a Psychological Shield Against Impulsive Shopping Online in Young Adults - Astri Nur Kusumastuti; Devvy Widyawati; Praesti Sedjo; Kenes Pranandari (Asosiasi Dosen Muda Indonesia, 2026)
The digital era has increased convenience in daily life, yet it may also intensify impulsive online purchasing when consumers respond automatically to persuasive cues and momentary urges. This study aimed to examine the influence of mindfulness on online impulsive buying among young adults, addressing the growing need to understand psychological factors that can help regulate consumer behavior in digital environments. Using a quantitative, cross-sectional design, data were collected through an online questionnaire from 210 respondents aged 18–30 years who were active users of online shopping platforms (minimum three transactions per month). Mindfulness was measured using the Five Facet Mindfulness Questionnaire (FFMQ), while online impulsive buying was assessed based on the cognitive and affective aspects proposed by Herabadi. Statistical analysis using SPSS indicated that mindfulness significantly influenced online impulsive buying (p < .001). These findings imply that mindfulness-oriented psychological interventions may function as a “digital brake,” supporting more reflective decision-making and reducing unplanned purchases in online marketplaces. The originality of this study lies in bridging cognitive psychology and digital consumer behavior by clarifying the role of mindfulness operationalized through FFMQ facets in explaining online impulsive buying among young adults.